Analisis Penerapan Koreksi Fiskal Atas Pendapatan, Beban, dan Pajak Tangguhan dalam Rangka Menghitung PPh Terutang PT. Gresik Migas (Perseroda) - Syahrani Amadea Iswanto; Suwandi Suwandi (Universitas 45 Surabaya, 2024)
Profit and loss report and balance sheet of PT. Gresik Migas, which adheres to Financial Accounting Standards (SAK), is included in financial reports based on research. Both internal and external parties use this report to calculate taxable income and make decisions. According to Income Tax (PSAK) No. 46, fiscal corrections are made to business income. These adjustments may be positive or negative. Fiscal adjustments address permanent and temporary gaps, resulting in fixed differences (retained earnings and transportation costs) and temporary differences (salary costs, taxes, communications, newspapers, cars, and human resource development). Higher profit margin for PT. Gresik Migas is affected by cost, sales and tax burdens of 0.20% in 2021–2022.